A hard carbon material and its preparation method and application
Through the reaction and carbonization of biomass materials after pickling and alcohol or ketone washing with metal cationic catalysts, hard carbon materials with excellent cycling and electrochemical properties were prepared, solving the problem of poor cycling performance of existing hard carbon materials in sodium ion batteries.
Patent Information
- Application Number
- CN202510032576.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-09
AI Technical Summary
When existing hard carbon materials are used for the negative electrode of sodium ion batteries, the circulation performance is poor, which limits the application prospects of sodium ion batteries.
After pickling and washing with alcohols or ketones, the biomass material is mixed with a catalyst containing transition metal cations or weak metal cations, reacted and carbonized, a hard carbon material with excellent structure is prepared.
The prepared hard carbon materials have good cycle performance, high specific capacity, high first efficiency, good rate performance, and wide application prospects.
Smart Images

Figure CN119430149B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a hard carbon material and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries have attracted much attention in the field of large-scale energy storage due to their low cost and abundant resources. However, due to the large ionic radius of Na, most electrode materials still have problems with poor ion transport kinetics and limited cycle life. At present, the main negative electrode materials include hard carbon, transition metal chalcogenides, metal compounds and organic compounds; among them, hard carbon with randomly oriented graphite layers and adjustable microstructures shows great commercial prospects in sodium-ion batteries due to its low voltage platform, scalable preparation, and stable chemical properties. Hard carbon is a non-graphitized carbon, usually described as a material containing microcrystals, graphite layers and nanopores. The complex disordered structure of hard carbon can produce tilted areas and platform areas during the charge and discharge process. However, at present, the hard carbon materials in the related technology are used in the negative electrode of sodium-ion batteries, and the cycle performance of the resulting batteries is poor, which to some extent limits the application prospects of sodium-ion batteries. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a method for preparing a hard carbon material, and the prepared hard carbon material is applied to a sodium ion battery, and the battery has good cycle performance.
[0004] The present invention also provides a hard carbon material.
[0005] The invention also provides a negative electrode material.
[0006] The invention also provides a negative electrode.
[0007] The present invention also provides a secondary battery.
[0008] In the first aspect of the present invention, a method for preparing a hard carbon material is proposed, comprising the following steps: a biomass material is washed with acid, alcohol or ketone, mixed with a material containing a cationic catalyst, reacted, and carbonized to obtain the hard carbon material, wherein the cations in the cationic catalyst include at least one of a transition metal cation or a weak metal cation.
[0009] The method for preparing the hard carbon material according to the embodiment of the present invention has at least the following beneficial effects:
[0010] The preparation method of the hard carbon material in the present invention is a method for preparing the hard carbon material based on biomass, and the obtained hard carbon material has the advantages of good structure, high cost-effectiveness, rich availability, environmental protection and the like. The biomass precursor is first treated by acid washing (such as nitric acid), and then washed with alcohols or ketones to remove some organic small molecules and invalid impurities such as tar. That is, by combining acid washing with alcohols or ketones, impurities and oil small molecules that are not conducive to the formation of a closed-cell structure of the hard carbon material can be removed, so that the material is more likely to be cracked during the carbonization process, and CO, CO2, etc. will be released during the cracking process. 2 , CH 4 , H 2 O and other gases are conducive to etching to produce a large number of open micropores. Then, by adding a catalytic substance containing metal cations or / and weak metal cations, after reaction and carbonization, a hard carbon material is obtained.
[0011] Among them, due to the catalytic effect of transition metal cations or / and weak metal cations in the preparation process, during the carbonization process: transition metal cations or / and weak metal cations will catalyze the carbon lattice distortion, create intrinsic defects, and make sp 2 Abundant defect sites are generated in the hybrid carbon network, thereby affecting the local electronic structure of the carbon skeleton, thereby enhancing the charge transfer ability; at the same time, the transition metal cations and / or weak metal cations catalyze the short-range graphite sheets to form long-range graphite layers, converting a large number of open micropores into closed nanopores. The weak metal elements in the weak metal cations (such as Bi, Sb, Sb) can alloy with sodium, have better sodium affinity activity, and exist in the carbon layer to help accelerate the transmission of sodium ions in the hard carbon, improve the kinetic properties of the obtained hard carbon negative electrode, and can further increase the capacity of the electrode. Therefore, the hard carbon material prepared by the present invention is used in a sodium ion battery, and the resulting sodium ion battery has the advantages of high specific capacity, high first efficiency, good rate performance, good cycle performance, and good application prospects.
[0012] In some embodiments of the present invention, the biomass material comprises at least one of coconut shells, straws, bagasse or wood chips.
[0013] In some embodiments of the present invention, the acid used in the pickling step is nitric acid.
[0014] Through the above implementation, the biomass material in the present invention adopts a combination of acid washing and alcohol washing to remove impurities and small oil molecules that are not conducive to the formation of a closed-cell structure of the hard carbon material. That is, nitrogen and transition metal cations and weak metal cations are used to regulate the structure of the hard carbon material, create internal defects, and make sp 2The abundant defect sites generated in the hybrid carbon network improve the sodium storage performance. At the same time, the weak metal elements in the weak metal cations can further improve the kinetic performance and sodium storage capacity by alloying with sodium. Among them:
[0015] The biomass material is washed with nitric acid to introduce nitrogen simultaneously, and then washed with alcohols or ketones to remove some small organic molecules and invalid impurities such as tar, making it easier to crack during the carbonization process. CO and CO will be released during the cracking process. 2 , CH 4 , H 2 O and other gases, which is conducive to etching to produce a large number of open micropores. Then, by adding a catalyst containing transition metal cations and / or weak metal cations, a chemical reaction occurs, and then high-temperature calcination and carbonization are performed to obtain hard carbon materials. During the carbonization process, on the one hand, the high temperature removes part of the nitrogen from the carbon skeleton, which can produce vacancies and non-hexagonal carbon rings. On the other hand, the transition metal cations and weak metal cations in the carbon skeleton will also catalyze the distortion of the carbon lattice and create internal defects, making sp 2 Abundant defect sites are generated in the hybrid carbon network, affecting the local electronic structure of the carbon skeleton, thereby enhancing the charge transfer ability; at the same time, transition metal cations and weak metal cations catalyze the formation of long-range graphite layers from short-range graphite sheets, converting a large number of open micropores into closed nanopores. In addition, the weak metal elements in the weak metal cations can also alloy with sodium, further improving the capacity and kinetic properties of the hard carbon material.
[0016] In some embodiments of the present invention, the alcohol comprises at least one of methanol or ethanol, and the ketone comprises acetone.
[0017] In some embodiments of the present invention, the transition metal cation includes at least one of an iron ion, a zinc ion, a copper ion, a manganese ion or a nickel ion.
[0018] In some embodiments of the present invention, the weak metal cation includes at least one of antimony ions, tin ions, or bismuth ions.
[0019] Through the above-mentioned implementation mode, in the present invention, the biomass material is washed with nitric acid, alcohols or ketones, and then mixed, reacted, and carbonized with a material of a functional cationic catalyst / additive to obtain a hard carbon material. Among them, the weak metal element in the weak metal cation can be alloyed with sodium, and it has a more excellent sodium affinity activity. The presence in the carbon layer helps to accelerate the transmission of sodium ions in the hard carbon, improve the kinetic properties of the prepared hard carbon negative electrode, and can further increase the capacity of the electrode. Therefore, the hard carbon material prepared by the present invention is used in a sodium ion battery, and the resulting sodium ion battery has the characteristics of high specific capacity, high initial efficiency, good rate performance, and good cycle performance.
[0020] In some embodiments of the present invention, the reaction temperature is 50-120°C.
[0021] In some embodiments of the present invention, the reaction time is 1 to 20 hours.
[0022] In some embodiments of the present invention, the carbonization temperature is 1200-1600°C.
[0023] In some embodiments of the present invention, the carbonization time is 1 to 10 hours.
[0024] The hard carbon material obtained in the present invention catalyzes the formation of long-range graphite layers from short-range graphite sheets under the catalytic action of a catalyst containing transition metal cations or / and weak metal cations, and converts a large number of open micropores into closed nanopores, so that the material not only has more platform area sodium storage space, but also can create intrinsic defects, so that sp 2 The abundant defect sites generated in the hybrid carbon network affect the local electronic structure of the carbon skeleton and enhance the charge transfer capability, thereby enriching the microstructure of reversible defects and greatly improving the comprehensive performance of hard carbon materials. In addition, the weak metal elements in the weak metal cations can also alloy with sodium metal to further enhance the sodium storage capacity and sodium ion transfer kinetics. When used in sodium ion batteries, the resulting sodium ion batteries exhibit high specific capacity and first efficiency, good rate performance, good cycle performance, and good application prospects.
[0025] In some embodiments of the present invention, the material containing the cationic catalyst includes a cationic salt and a complexing agent.
[0026] In some embodiments of the present invention, the cationic salt includes at least one of a cationic acetate, a cationic sulfate, a cationic hydrochloride, or a cationic phosphate.
[0027] In some embodiments of the present invention, the chelating agent includes at least one of humic acid, fulvic acid, phytic acid or folic acid.
[0028] In some embodiments of the present invention, the mass ratio of the biomass material to the cationic salt is 1:(0.01~2).
[0029] In some embodiments of the present invention, the mass ratio of the biomass material to the complexing agent is 1:(0.1-2), such as 1:(0.1-1).
[0030] In some embodiments of the present invention, the material containing the cationic catalyst further comprises an organic solvent.
[0031] In some embodiments of the present invention, the preparation method comprises the following steps:
[0032] S1, taking a biomass material, mixing it with a nitric acid solution, washing it with water until it is neutral, and then washing it with an alcohol or a ketone to obtain a precursor material;
[0033] S2, mixing the precursor material, cationic salt, complexing agent and organic solvent, stirring at 50-120° C. for 1-20 h to obtain a mixed material I;
[0034] S3, the mixed material I is subjected to solid-liquid separation and then carbonized in an inert atmosphere to obtain the hard carbon material.
[0035] In the present invention, hard carbon materials are prepared by acid washing, low temperature stirring and carbonization. Specifically, the biomass material is first washed with nitric acid to introduce nitrogen into it (which is beneficial to remove some nitrogen from the carbon skeleton in the subsequent carbonization step, and can produce vacancies and non-hexagonal carbon rings), and then washed with alcohols or ketones (such as ethanol) to remove some small organic molecules and invalid impurities such as tar, making it easier to crack during the carbonization process, and CO, CO 2 , CH 4 , H 2 O and other gases are conducive to etching to produce a large number of open micropores. Then, by adding a catalyst containing transition metal cations or / and weak metal cations, the biomass material is fully stirred in an organic solvent at a certain temperature, so that the catalytic substance and the biomass material react evenly and fully, and then carbonize to obtain a hard carbon material. During the carbonization process, on the one hand, the high temperature removes part of the nitrogen from the carbon skeleton, which can produce vacancies and non-hexagonal carbon rings. On the other hand, the transition metal cations or / and weak metal cations will also catalyze the distortion of the carbon lattice, creating internal defects, making sp 2 Abundant defect sites are generated in the hybrid carbon network, affecting the local electronic structure of the carbon skeleton, thereby enhancing the charge transfer ability; at the same time, transition metal cations and / or weak metal cations can catalyze short-range graphite sheets to form long-range graphite layers, converting a large number of open micropores into closed nanopores; in addition, the weak metal elements in the weak metal cations can also undergo alloying reactions with sodium metal, further improving the sodium storage capacity and sodium ion transport kinetics, and obtaining hard carbon materials with excellent performance.
[0036] In some embodiments of the present invention, in step S1, the biomass material is crushed to obtain biomass powder, which is then mixed with the nitric acid solution.
[0037] In some embodiments of the present invention, the particle size of the biomass powder is 10-200 μm, such as 20-50 μm.
[0038] In some embodiments of the present invention, in step S1, the ratio of the amount of the biomass material to the amount of the nitric acid solution is 1 g: (20-100) mL.
[0039] In some embodiments of the present invention, in step S1, the concentration of nitric acid in the nitric acid solution is 0.5-2 mol / L.
[0040] In some embodiments of the present invention, in step S1, the nitric acid solution is an aqueous nitric acid solution.
[0041] In some embodiments of the present invention, in step S1, the alcohol is ethanol, wherein in the ethanol washing step, the ethanol washing solution obtained after washing is colorless, and after drying, the precursor material is obtained.
[0042] In some embodiments of the present invention, in step S2, the ratio of the amount of the biomass material to the amount of the organic solvent is 1 g: (50-200) mL.
[0043] The second aspect of the present invention provides a hard carbon material, which is prepared by adopting the above-mentioned preparation method of the hard carbon material.
[0044] In some embodiments of the present invention, the particle size of the hard carbon material is 10-100 μm, such as 20-50 μm.
[0045] In some embodiments of the present invention, the hard carbon material includes vacancies and non-hexagonal carbon rings.
[0046] According to a third aspect of the present invention, a negative electrode material is provided, comprising the hard carbon material.
[0047] In a fourth aspect of the present invention, a negative electrode is provided, comprising the hard carbon material or the negative electrode material.
[0048] In some embodiments of the present invention, the negative electrode includes a negative electrode active layer, and the negative electrode active layer includes a hard carbon material.
[0049] In some embodiments of the present invention, the negative electrode includes a negative electrode current collector and a negative electrode active layer that are stacked.
[0050] According to a fifth aspect of the present invention, a secondary battery is provided, comprising the hard carbon material or the negative electrode material or the negative electrode.
[0051] In some embodiments of the present invention, the secondary battery includes at least one of a lithium ion battery or a sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0053] Figure 1 Schematic diagram of the preparation process of the hard carbon material in the embodiments and comparative examples of the present invention;
[0054] Figure 2 This is a TEM image of the hard carbon material obtained in Example 8 of the present invention;
[0055] Figure 3 This is the XRD pattern of the hard carbon material obtained in Example 8 of the present invention;
[0056] Figure 4 This is a Raman image of the hard carbon material obtained in Example 8 of the present invention;
[0057] Figure 5 This is a charge and discharge curve diagram of a battery obtained by using the hard carbon material of Example 8 of the present invention as a negative electrode material for a sodium ion battery. DETAILED DESCRIPTION
[0058] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0059] The experimental methods without specific conditions in the following embodiments and test examples are generally based on conventional conditions in the art or conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets.
[0060] Example 1
[0061] This embodiment discloses a hard carbon material (abbreviated as: ANHC / AT@Fe-1400), the preparation process of which specifically includes:
[0062] First, the coconut shell is crushed and sieved to obtain a powder (particle size is 20~50μm), then added to a 1mol / L nitric acid aqueous solution and stirred for 12 hours (the stirring speed is 300~900 rpm, and the ratio of coconut shell to nitric acid aqueous solution is 1g:20mL), then washed with deionized water until neutral, washed with ethanol until the ethanol solution obtained after washing is colorless, and then dried to obtain the treated biomass material. Then, according to the mass ratio of the treated biomass material: phytic acid: ferrous acetate of 1:1:0.1, it is added to methanol (the ratio of the biomass material to methanol is 1g:50mL, stirred at 80℃ for 5 hours, solid-liquid separation, and then heated to 1400℃ (carbonization temperature) in a nitrogen atmosphere, the heating rate is 2℃ / min, and the carbonization time is 2h to obtain a hard carbon material.
[0063] This embodiment also discloses a negative electrode material, including the hard carbon material prepared in this embodiment.
[0064] This embodiment also discloses a negative electrode, including the hard carbon material or negative electrode material prepared in this embodiment.
[0065] This embodiment also discloses a sodium ion battery, including the hard carbon material of this embodiment or the negative electrode material of this embodiment or the negative electrode of this embodiment.
[0066] Example 2
[0067] This embodiment discloses a hard carbon material (abbreviated as: ANHC / AT@Zn-1400), which is different from the embodiment 1 only in that the same mass of zinc acetate is used to replace the iron acetate in the embodiment 1. The rest is the same as the embodiment 1.
[0068] This embodiment also discloses a negative electrode material, including the hard carbon material prepared in this embodiment.
[0069] This embodiment also discloses a negative electrode, including the hard carbon material or negative electrode material prepared in this embodiment.
[0070] This embodiment also discloses a sodium ion battery, including the hard carbon material of this embodiment or the negative electrode material of this embodiment or the negative electrode of this embodiment.
[0071] Example 3
[0072] This embodiment discloses a hard carbon material (abbreviated as: ANHC / AT@Mn-1400), which is different from the embodiment 1 only in that an equal mass of manganese acetate is used to replace the iron acetate in the embodiment 1. The rest is the same as the embodiment 1.
[0073] This embodiment also discloses a negative electrode material, including the hard carbon material prepared in this embodiment.
[0074] This embodiment also discloses a negative electrode, including the hard carbon material or negative electrode material prepared in this embodiment.
[0075] This embodiment also discloses a sodium ion battery, including the hard carbon material of this embodiment or the negative electrode material of this embodiment or the negative electrode of this embodiment.
[0076] Example 4
[0077] This embodiment discloses a hard carbon material (abbreviated as: ANHC / AT@Ni-1400), which is different from the embodiment 1 only in that the same mass of nickel acetate is used to replace the iron acetate in the embodiment 1. The rest is the same as the embodiment 1.
[0078] This embodiment also discloses a negative electrode material, including the hard carbon material prepared in this embodiment.
[0079] This embodiment also discloses a negative electrode, including the hard carbon material or negative electrode material prepared in this embodiment.
[0080] This embodiment also discloses a sodium ion battery, including the hard carbon material of this embodiment or the negative electrode material of this embodiment or the negative electrode of this embodiment.
[0081] Example 5
[0082] This embodiment discloses a hard carbon material (abbreviated as: ANHC / AT@Cu-1400), which is different from the embodiment 1 only in that the same mass of copper acetate is used to replace the iron acetate in the embodiment 1. The rest is the same as the embodiment 1.
[0083] This embodiment also discloses a negative electrode material, including the hard carbon material prepared in this embodiment.
[0084] This embodiment also discloses a negative electrode, including the hard carbon material or negative electrode material prepared in this embodiment.
[0085] This embodiment also discloses a sodium ion battery, including the hard carbon material of this embodiment or the negative electrode material of this embodiment or the negative electrode of this embodiment.
[0086] Example 6
[0087] This embodiment discloses a hard carbon material (abbreviated as: ANHC / AT@Bi-1400), which is different from the embodiment 1 only in that bismuth acetate of equal mass is used to replace the iron acetate in the embodiment 1. The rest is the same as the embodiment 1.
[0088] This embodiment also discloses a negative electrode material, including the hard carbon material prepared in this embodiment.
[0089] This embodiment also discloses a negative electrode, including the hard carbon material or negative electrode material prepared in this embodiment.
[0090] This embodiment also discloses a sodium ion battery, including the hard carbon material of this embodiment or the negative electrode material of this embodiment or the negative electrode of this embodiment.
[0091] Example 7
[0092] This embodiment discloses a hard carbon material (abbreviated as: ANHC / AT@Sn-1400), which is different from the embodiment 1 only in that tin acetate of the same mass is used to replace the ferric acetate in the embodiment 1. The rest is the same as the embodiment 1.
[0093] This embodiment also discloses a negative electrode material, including the hard carbon material prepared in this embodiment.
[0094] This embodiment also discloses a negative electrode, including the hard carbon material or negative electrode material prepared in this embodiment.
[0095] This embodiment also discloses a sodium ion battery, including the hard carbon material of this embodiment or the negative electrode material of this embodiment or the negative electrode of this embodiment.
[0096] Example 8
[0097] This embodiment discloses a hard carbon material (abbreviated as: ANHC / AT@Sb-1400), which is different from the embodiment 1 only in that an equal mass of antimony acetate is used to replace the ferric acetate in the embodiment 1. The rest is the same as the embodiment 1.
[0098] This embodiment also discloses a negative electrode material, including the hard carbon material prepared in this embodiment.
[0099] This embodiment also discloses a negative electrode, including the hard carbon material or negative electrode material prepared in this embodiment.
[0100] This embodiment also discloses a sodium ion battery, including the hard carbon material of this embodiment or the negative electrode material of this embodiment or the negative electrode of this embodiment.
[0101] Comparative Example 1
[0102] This comparative example discloses a hard carbon material (abbreviated as: HC-1200), and its preparation process specifically includes: firstly, crushing and sieving coconut shells to obtain powder with a particle size of 20-50 μm, washing and drying with deionized water, and then heating to 1200°C (carbonization temperature) in a nitrogen atmosphere, with a heating rate of 2°C / min and a carbonization time of 2h to obtain the hard carbon material HC-1200.
[0103] Comparative Example 2
[0104] This comparative example discloses a hard carbon material (abbreviated as: HC-1400), which is different from comparative example 1 only in that the carbonization temperature in this comparative example is 1400° C., and the rest is the same as comparative example 1.
[0105] Comparative Example 3
[0106] This comparative example discloses a hard carbon material (abbreviated as: HC-1600), which is different from comparative example 1 only in that the carbonization temperature in this comparative example is 1600° C., and the rest is the same as comparative example 1.
[0107] Comparative Example 4
[0108] The comparative example discloses a hard carbon material (abbreviated as: NHC-1200), and its preparation process specifically includes: firstly crushing the coconut shell material, sieving to obtain a powder with a particle size of 20-50 μm, then adding it into a 1 mol / L nitric acid aqueous solution and stirring for 12 hours (the stirring speed can be 300-900 rpm), first washing with deionized water to neutrality, heating to 1200°C (carbonization temperature) in a nitrogen atmosphere, the heating rate is 2°C / min, and the carbonization time is 2h to obtain the hard carbon material NHC-1200.
[0109] Comparative Example 5
[0110] This comparative example discloses a hard carbon material (abbreviated as: NHC-1400), which is different from comparative example 4 only in that the carbonization temperature in this comparative example is 1400° C., and the rest is the same as comparative example 4.
[0111] Comparative Example 6
[0112] This comparative example discloses a hard carbon material (abbreviated as: NHC-1600), which is different from comparative example 4 only in that the carbonization temperature in this comparative example is 1600° C., and the rest is the same as comparative example 4.
[0113] Comparative Example 7
[0114] The present comparative example discloses a hard carbon material (abbreviated as: ANHC-1200), and its preparation process specifically includes: firstly crushing the coconut shell material, sieving to obtain a powder with a particle size of 20-50 μm, then adding it into a 1 mol / L nitric acid aqueous solution and stirring for 12 hours (the stirring speed can be 300-900 rpm), first washing with deionized water to neutrality, then washing with ethanol until the ethanol solution is colorless after washing, then drying, and then heating to 1200°C (carbonization temperature) in a nitrogen atmosphere, the heating rate is 2°C / min, and the carbonization time is 2h, to obtain the hard carbon material ANHC-1200.
[0115] Comparative Example 8
[0116] This comparative example discloses a hard carbon material (abbreviated as: ANHC-1400), which is different from comparative example 7 only in that the carbonization temperature in this comparative example is 1400° C., and the rest is the same as comparative example 7.
[0117] Comparative Example 9
[0118] This comparative example discloses a hard carbon material (abbreviated as: ANHC-1600), which is different from comparative example 7 only in that the carbonization temperature in this comparative example is 1600° C., and the rest is the same as comparative example 7.
[0119] The particle size of the hard carbon material prepared in the embodiment is 20-50 μm. The schematic diagram of the preparation process of the hard carbon material in the above embodiment and comparative example is as follows: Figure 1 shown.
[0120] Test example
[0121] This test example tests the performance of the hard carbon materials in the embodiments and comparative examples, specifically including:
[0122] (1) Figure 2 This is a TEM image of the hard carbon material obtained in Example 8; Figure 3 The XRD pattern of the hard carbon material obtained in Example 8 has diffraction peaks at 23° and 43°, corresponding to the (002) peak and (100) peak of the hard carbon material, respectively, and has typical hard carbon structural characteristics; Figure 4 This is the Raman image of the hard carbon material obtained in Example 8, at 1350 cm -1 and 1595cm -1 The two peaks at , correspond to the D band related to the defects in hard carbon and the G band related to the degree of graphitization, respectively. The area ratio of the D band to the G band is D / I G It is often used to characterize the degree of defects or graphitization of hard carbon, where I D / I G The smaller the value, the smaller the degree of defect, that is, the higher the degree of graphitization. The I calculated in Example 8 D / I G The value is 1.26, which is relatively small, indicating that the hard carbon material obtained in Example 8 has a higher degree of graphitization, which also proves the catalytic effectiveness of the metal cation catalyst used in the present invention.
[0123] (2) The hard carbon materials prepared in the comparative examples and embodiments were used as negative electrode materials for sodium ion batteries, and the initial specific capacity, initial coulombic efficiency and capacity retention rate after 100 cycles of the sodium ion batteries were tested. The test results are shown in Table 1 below. Figure 5 The charge and discharge curve of the battery obtained by using the hard carbon material of Example 8 as the negative electrode material of the sodium ion battery is shown in FIG. Figure 5 It can be seen that the hard carbon material of Example 8 is used as the negative electrode of the sodium ion battery, and the obtained battery has a high first-cycle reversible capacity of 376 mAh / g and a high first coulombic efficiency of 92.5%, which is significantly better than the test results of the battery obtained in Comparative Example 8 without using a metal cation catalyst. At the same time, combined with Table 1, it can be seen that compared with Comparative Example 8, the capacity retention rate of the battery obtained in Example 8 after 100 cycles is also increased from 92.9% to 98.2%, which fully demonstrates the effectiveness of the metal cation catalyst used in the present invention in improving the electrochemical performance of the hard carbon material.
[0124] Table 1
[0125]
[0126] The electrochemical performance of the sodium ion battery half-cell was tested by first placing a standard CR-2032 coin cell in a solution filled with Ar (H 2 O<10 -2 ppm,O 2 <10 -2 The battery was assembled in a glove box with a concentration of 100 ppm. Specifically, for the half-cell, the hard carbon material, conductive carbon and polyvinylidene fluoride (PVDF) binder prepared in each comparative example and embodiment were uniformly mixed in a weight ratio of 8:1:1, dispersed in N-methylpyrrolidone (NMP) to prepare an electrode slurry, which was then coated on a 20µm copper foil and vacuum dried at 120°C overnight. The surface mass loading of the electrode material on the copper foil was about 1.0~1.5 mg cm -2 The half-cell assembly uses glass fiber as a separator (50µm), pure metal Na as a counter electrode, and each button cell uses 100μL of electrolyte, which is a mixture of hexafluorophosphate (NaPF 6 ) was dissolved in ethylene glycol dimethyl ether (DME), and the concentration of hexafluorophosphate in the obtained electrolyte was 1 mol / L. Constant current charge and discharge measurements were performed at room temperature in the voltage range of 0.01~2.5V using the Neware battery test system.
[0127] Compared with Mn, Ni and Cu, when Fe, Zn, Bi, Sb and Sn are used, the carbon material has a more suitable interlayer spacing and a curved long-layer graphite-like structure under the action of Fe, Zn, Bi, Sb and Sn, and the bending and contraction of cellulose during the carbonization process creates a richer closed nanopore structure; in addition, Bi, Sb and Sn are metals that can be alloyed with sodium and have better sodium affinity. Their presence in the carbon layer helps to accelerate the transmission of sodium ions in the hard carbon, thereby improving the transfer kinetics of sodium ions and can further increase the capacity of the electrode.
[0128] In the present invention, after the biomass material is fully dried and crushed, the biomass precursor is washed with nitric acid to simultaneously introduce nitrogen into it; and then some organic small molecules and invalid impurities such as tar are removed by alcohol washing or ketone washing, so that cracking is more likely to occur during the carbonization process, and CO and CO will be released during the cracking process. 2 , CH 4 , H 2O and other gases are conducive to etching to produce a large number of open micropores. Then, by adding a catalyst containing transition metal cations and weak metal cations, the precursor is fully stirred in an organic solvent at a certain temperature to allow the catalyst and precursor to react evenly and fully, and then high-temperature calcination and carbonization are performed to obtain the target hard carbon material. During the carbonization process, on the one hand, high temperature allows the removal of some nitrogen from the carbon skeleton to produce vacancies and non-hexagonal carbon rings. On the other hand, the transition metal cations and / or weak metal cations will also catalyze the distortion of the carbon lattice, creating intrinsic defects, making sp 2 Abundant defect sites are generated in the hybrid carbon network, affecting the local electronic structure of the carbon skeleton, thereby enhancing the charge transfer ability; at the same time, transition metal cations and / or weak metal cations catalyze the formation of long-range graphite layers from short-range graphite sheets, converting a large number of open micropores into closed nanopores; in addition, weak metal elements can also alloy with sodium metal, which is beneficial to further improve the kinetic properties and capacity of hard carbon materials.
[0129] Among them, the catalytic formation of long-range graphite layers from short-range graphite sheets during pyrolysis can not only enrich the internal defects of hard carbon (such as a large number of vacancies and non-hexagonal carbon rings), but also generate many nanopores for storing sodium ions, which is conducive to better sodium ion intercalation. 2 Abundant defect sites are generated in the hybrid carbon network, thereby affecting the local electronic structure of the carbon skeleton, thereby enhancing the charge transfer capability, and making the material have excellent rate performance; in addition, alloying of weak metal elements and sodium can further improve the kinetic performance and sodium storage capacity of the hard carbon negative electrode. The hard carbon material prepared by the present invention is used in a sodium ion battery, and the obtained sodium ion battery has high specific capacity, high first efficiency and excellent rate performance.
[0130] Therefore, the present invention obtains a microstructure with both appropriate interlayer spacing and abundant internal defects through simple pickling, stirring and one-step carbonization, which greatly improves the comprehensive performance of the hard carbon material. Among them, the hard carbon material is generated by one-step carbonization, omitting the pre-carbonization step and saving the manufacturing cost.
[0131] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a hard carbon material, characterized in that: The method comprises the following steps: washing a biomass material with acid, alcohol or ketone, mixing it with a material containing a cationic catalyst, reacting it and carbonizing it to obtain the hard carbon material, wherein the acid used in the acid washing step is nitric acid, the material containing a cationic catalyst comprises a cationic salt and a complexing agent, and the cations in the cationic salt comprise at least one of a transition metal cation or a weak metal cation; during the carbonization process, the cations in the cationic salt catalyze the distortion of the carbon lattice.
2. The method for preparing a hard carbon material according to claim 1, characterized in that: The biomass material includes at least one of coconut shells, straw, bagasse or wood chips.
3. The method for preparing a hard carbon material according to claim 1, characterized in that: The alcohol includes at least one of methanol and ethanol, and the ketone includes acetone.
4. The method for preparing a hard carbon material according to claim 1, characterized in that: The transition metal cation includes at least one of iron ion, zinc ion, copper ion, manganese ion or nickel ion.
5. The method for preparing a hard carbon material according to claim 1, characterized in that: The weak metal cation includes at least one of antimony ions, tin ions or bismuth ions.
6. The method for preparing a hard carbon material according to claim 1, characterized in that: The reaction temperature is 50-120°C.
7. The method for preparing a hard carbon material according to claim 1, characterized in that: The reaction time is 1 to 20 hours.
8. The method for preparing a hard carbon material according to claim 1, characterized in that: The carbonization temperature is 1200-1600°C.
9. The method for preparing a hard carbon material according to claim 1, characterized in that: The carbonization time is 1 to 10 hours.
10. The method for preparing a hard carbon material according to claim 1, characterized in that: The cationic salt includes at least one of cationic acetate, cationic sulfate, cationic hydrochloride or cationic phosphate.
11. The method for preparing a hard carbon material according to claim 1, characterized in that: The complexing agent includes at least one of humic acid, fulvic acid, phytic acid or folic acid.
12. The method for preparing a hard carbon material according to claim 1, characterized in that: The mass ratio of the biomass material to the complexing agent is 1:(0.1-2).
13. The method for preparing a hard carbon material according to claim 1, characterized in that: The preparation method comprises the following steps: S1, taking a biomass material, mixing it with a nitric acid solution, washing it with water until it is neutral, and then washing it with an alcohol or a ketone to obtain a precursor material; S2, mixing the precursor material, cationic salt, complexing agent and organic solvent, stirring at 50-120° C. for 1-20 h to obtain a mixed material I; S3, the mixed material I is separated into solid and liquid, and then carbonized in an inert atmosphere to obtain the hard carbon material.
14. A hard carbon material, characterized in that: The method comprises the following steps: preparing the product by adopting the preparation method according to any one of claims 1 to 13.
15. The hard carbon material according to claim 14, characterized in that The particle size of the hard carbon material is 10-100 μm.
16. A negative electrode material, characterized in that: It includes the hard carbon material obtained by the preparation method according to any one of claims 1 to 13 or the hard carbon material according to any one of claims 14 to 15.
17. A negative electrode, characterized in that: It comprises the hard carbon material obtained by the preparation method according to any one of claims 1 to 13, the hard carbon material according to any one of claims 14 to 15, or the negative electrode material according to claim 16.
18. A secondary battery, characterized in that: It comprises a hard carbon material obtained by the preparation method according to any one of claims 1 to 13, or a hard carbon material according to any one of claims 14 to 15, or a negative electrode material according to claim 16, or a negative electrode according to claim 17.
Citation Information
Patent Citations
Wild pepper hard carbon sodium / potassium ion negative electrode material as well as preparation method and application thereof
CN108975304A
Preparation method of sodium ion battery negative electrode material with high first efficiency
CN117361497A
Positive electrode material and preparation method and application thereof
CN117712303A